DETERMINAN KUALITAS AUDIT DAN FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDITEE SATISFACTION (STUDI EMPIRIS PADA AUDITOR INTERNAL BANK UMUM SYARIAH DI INDONESIA) - Hermi , (Media Riset Akuntansi, Auditing & Informasi, 2014)
The purpose of this study is to analyze the influence of Independence, Competence and Islamic work Ethics partially and simultaneously to the Audit Quality . The next purpose is to analyze the influence of Audit Quality, Audit Services Portfolio and Audit Firm Reputation partially and simultaneously against Auditee Satisfaction on Islamic Banks in Indonesia. This study is expected to provide benefit to the development of knowledge, particularly in the field of accounting and auditing, Government, Islamic Bank, Indonesian Institute of Accountants (IAI ), Indonesian Institute of Certified Public Accountants (IAP ), the auditors and the Audit Firm (KAP). The results are expected to provide information for various parties accurately and meaningfully as a solution to determine the variables that affect the Auditee Satisfaction and Audit Quality at Islamic Bank in Indonesia. Limitations of the study include: (1) The extent of the problem which studied in determining the factors that can affect the Audit Quality and Auditee Satisfaction in Islamic Bank in Indonesia , (2) Limitation of the study lies in the data acquisition, (3) This study only emphasized the perception of the factors that may affect Audit Quality and Auditee Satisfaction.This study used primary data through questionnaires with the population of internal auditors of Islamic Banks in Indonesia. This study used a quantitative approach and in terms of the type of investigation, this study is causal. Based on the time horizon the study is cross-sectional (one - shot ) because the data was collected only once . Before using the data to test hypothesis, the validity and reliability test should be done first.Data analysis uses Structural Equation Model (SEM) supported by AMOS software. Based on the test results, it shows that Independence, Competence and Islamic work Ethics partially or simultaneously affect the Audit Quality significantly. The next stage of testing Audit Quality partially has no significant effect on the Auditee Satisfaction. While Audit Service Portfolio and Audit Firm Reputation either partially or simultaneously have significant effect on the Auditee Satisfaction. Simultaneously the three variables Audit Quality, and Audit Services Portfolio and Reputation of Audit Firm have significant effect on the Auditee Satisfaction.